2015
DOI: 10.1016/j.jconrel.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Multistage vector (MSV) therapeutics

Abstract: One of the greatest challenges in the field of medicine is obtaining controlled distribution of systemically administered therapeutic agents within the body. Indeed, biological barriers such as physical compartmentalization, pressure gradients, and excretion pathways adversely affect localized delivery of drugs to pathological tissue. The diverse nature of these barriers requires the use of multifunctional drug delivery vehicles that can overcome a wide range of sequential obstacles. In this review, we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 125 publications
(194 reference statements)
0
51
0
Order By: Relevance
“…Recently, multistage nanovectors (i.e. disk-shaped porous silicon [3335]) were developed to strategically overcome the body’s biological barriers through unique size and shape tailoring (Figure 1). Researchers demonstrated that the degradation rates increase significantly as pore size increases [36].…”
Section: Significance and Overview Of Nanotechnologymentioning
confidence: 99%
“…Recently, multistage nanovectors (i.e. disk-shaped porous silicon [3335]) were developed to strategically overcome the body’s biological barriers through unique size and shape tailoring (Figure 1). Researchers demonstrated that the degradation rates increase significantly as pore size increases [36].…”
Section: Significance and Overview Of Nanotechnologymentioning
confidence: 99%
“…In particular, our group previously demonstrated cellular membranes of circulating leukocytes could be easily isolated and transferred onto the surface of synthetic nanocarriers while maintaining key biological functions. These carriers, referred to as Leukolike Vectors (LLV) [4], are composed of a loadable [5], biodegradable [6, 7], and biocompatible [8, 9] multistage nanovector (MSV) [1013] core with a proteolipid outer shell purified from leukocyte cell membrane (CM). This outer layer was shown to retain membrane proteins [14] that are critical for increased adhesion towards inflamed endothelium [15] while also providing prolonged circulation time [16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous nanoparticles have been designed for medical applications, and several have received clinical approval [9,10]. Here, we have used a porous silicon-based multistage vector (MSV), rationally designed to deliver therapeutic agents to neoplastic tissue [11,12]. The MSV nanodelivery system was introduced in 2008 as one of the first platforms in which various components can sequentially be released to overcome biological barriers.…”
Section: Introductionmentioning
confidence: 99%
“…it operates as a delivery system for nanoparticles [12]. This multifaceted approach enables the MSV to address various transport barriers in the body [29], resulting in increased exposure of drugs to pathological tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation